Sensory Test on 3 Types of Functional Beverages - Nunuk Helilusiatiningsih; Sumarji (East Asian Journal of Multidisciplinary Research, 2023)
The research method used was a qualitative test consisting of a visual test (color) and a sensory test including aroma and taste. The research treatments were M1, M2,  M3. The results of the study showed that were as follows: M1, Ginger Tea: color, aroma, taste tests, namely 4 people really liked it, 14 people liked it, 2 people didn't like it; M2, Lemongrass tea: Color test, aroma test, namely 2 people really like it, 17 people like it, 1 person doesn't like it, the taste test shows 2 people really like it, 16 people like it and 2 people don't like it; M3, Lemongrass ginger tea: color, aroma, taste test yielded 13 people really liked it, 6 people liked it, 1 person didn't like it. So the functional drink most preferred by consumers was M3.